Nunca llueve en Lima, fabrico mi lluvia - Avalos Carrillo, Guillermina (Pontificia Universidad Católica del Perú, 2025)
Lima is a city where rain is like an elusive whisper, where humidity floods nearly everything without a single drop ever falling. In 2020, when the world came to a halt, I found myself trapped on the seventh floor of the Coloso de Tacna, the tallest building at the intersection of Tacna and Colmena in Lima’s Historic Center. That bustling, lively crossing had suddenly fallen silent. From the window, I observed the urban landscape, longing for the drizzles that once caressed my childhood. With the world closed off and my view restricted, I explored various techniques to photograph an imagined summer rain, one that only existed in my mind. This was a fabricated, fictional rain, much in line with Fontcuberta’s perspective that «every photograph is a fiction presented as truth» (1997, p. 15), and Baudrillard’s principle of simulation, which claims that a photographic image is, rather than representation, fiction (Damiano, 2014). So, I crafted a fictional rain, a fictional record, using water vapor and translucent surfaces to create ephemeral drops that slide slowly in front of the city. The light’s refraction in these drops multiplies Lima’s architecture, capturing the buildings in fleeting capsules, allowing the city to be seen through drops that gently trickle down.

Lima es una ciudad donde la lluvia es como un susurro esquivo, donde la humedad lo inunda casi todo sin llover jamás. En 2020, cuando el mundo se detuvo, quedé atrapada en el séptimo piso del Coloso de Tacna, el edificio más alto de la intersección de Tacna y Colmena, en el Centro Histórico de Lima. Ese cruce de avenidas, normalmente bullicioso y lleno de vida, había sido silenciado de golpe. Desde la ventana, observaba el paisaje urbano, añorando las lloviznas que acariciaron mi infancia. Con el mundo cerrado y la vista limitada, exploré diversos recursos para fotografiar una inexistente lluvia de verano, una que solo podía imaginar. Se trata de una lluvia fabricada, ficcional, muy acorde con la mirada de Fontcuberta, quien sostiene que «toda fotografía es una ficción que se presenta como verdadera» (1997, p. 15), y con el principio de simulación de Baudrillard, quien afirma que la imagen fotográfica, más que representación, es una ficción (Damiano, 2014). Así, fabriqué una lluvia ficticia, un registro ficcional, creando con vapor de agua y soportes traslúcidos gotas efímeras que se deslizan lentamente frente a la ciudad. La refracción de la luz en estas gotas multiplica la arquitectura limeña, al atrapar los edificios en cápsulas efímeras que permiten ver la ciudad a través de gotas que se deslizan lentamente.
It Never Rains in Lima, I Make My Own Rain
Keywords: Fictional rain; Conceptual photography; Urban Lima; Visual simulation; Lluvia ficticia; Fotografía conceptual; Lima urbana; Simulación visual; https://purl.org/pe-repo/ocde/ford#6.04.00